2017
DOI: 10.1038/s41467-017-01574-5
|View full text |Cite
|
Sign up to set email alerts
|

PTEN is a protein phosphatase that targets active PTK6 and inhibits PTK6 oncogenic signaling in prostate cancer

Abstract: PTEN activity is often lost in prostate cancer. We show that the tyrosine kinase PTK6 (BRK) is a PTEN substrate. Phosphorylation of PTK6 tyrosine 342 (PY342) promotes activation, while phosphorylation of tyrosine 447 (PY447) regulates auto-inhibition. Introduction of PTEN into a PTEN null prostate cancer cell line leads to dephosphorylation of PY342 but not PY447 and PTK6 inhibition. Conversely, PTEN knockdown promotes PTK6 activation in PTEN positive cells. Using a variety of PTEN mutant constructs, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 64 publications
3
53
0
Order By: Relevance
“…Therefore, the loss of PTEN, which occurs in the major of the tumors, is correlated with tumor aggressiveness and low response to therapy. In prostate cancer studies, PTEN has been shown to ameliorate the malignant phenotype by dephosphorylating the activator residue of PTK6 (Tyr 342), a kinase related to a cancer aggressive phenotype [94]. In addition, other oncogenic kinases, such as PDGFR and FAK, have been reported as a substrate of PTEN [95,96].…”
Section: Ptps That Act As Tumor Suppressorsmentioning
confidence: 99%
“…Therefore, the loss of PTEN, which occurs in the major of the tumors, is correlated with tumor aggressiveness and low response to therapy. In prostate cancer studies, PTEN has been shown to ameliorate the malignant phenotype by dephosphorylating the activator residue of PTK6 (Tyr 342), a kinase related to a cancer aggressive phenotype [94]. In addition, other oncogenic kinases, such as PDGFR and FAK, have been reported as a substrate of PTEN [95,96].…”
Section: Ptps That Act As Tumor Suppressorsmentioning
confidence: 99%
“…When we inspected the data from the p110α overexpression study, we noted that ~10% of variants were not scored with high confidence. For example, the G129R mutation is well characterized as having a complete loss of PTEN function [32,33]. Yet in the p110α study it was not classified as a likely damaging with high confidence.…”
Section: Comparison With Existing Variant Analysesmentioning
confidence: 99%
“…Moreover, we found that PTK6 and SRMS within the same upstream module. The product of two genes work closely together as intracellular kinases (32) and promotes invasive prostate cancer (33). However, they are rarely studied in the context of glioma and immune response.…”
Section: Orn Characterized Common Mechanisms In Cancermentioning
confidence: 99%